ANALISIS EFISIENSI USAHA PERAJIN CAPING DI DESA BANJARSARI KECAMATAN AJIBARANG KABUPATEN BANYUMAS - Untung Kumorohadi; Eling Purwanto Jati (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2006)
The aims of this research are first, to know degree of business efficiency level of Traditional Hat (Caping) Crafters at Banjarsari Village Ajibarang District Banyumas Regency. Second, to know the income proportion of Traditional Hat (Caping) Crafters at Banjarsari Village Ajibarang District Banyumas Regency is less than fifty percent than the total family income. The tools analysis proposed in this research for knowing the degree of business efficiency level of Traditional Hat (Caping) Crafters is benefit cost ratio analysis (B/C ratio), whereas for knoing the income proportion of Traditional Hat (Caping) Crafters at Banjarsari toward the total family income is used comparison method (percentage). The results of this research at Traditional Hat (Caping) are first, the average of business efficiency level is efficient and the level of efficiency is 1,45. Then, the income proportion of Traditional Hat (Caping) Crafters at Banjarsari Village Ajibarang District Banyumas Regency is 38,33 percent. It means that 61,66 percent income of Traditional Hat (Caping) Crafters comes from the other businesses. Based on the findings, it can be suggested that Traditional Hat (Caping) Crafters at Banjarsari Village Ajibarang District Banyumas Regency should be kept maintaining and even improved by giving guidance, training and education to Traditional Hat (Caping) Crafters. The government should help the income of Traditional Hat (Caping) Crafters at Banjarsari Village Ajibarang District Banyumas Regency by establishing a crafters cooperative. As a result, the crafter cooperative can manage the crafters income, and finally the income proportion of Traditional Hat (Caping) Crafters at Banjarsari Village Ajibarang District Banyumas Regency will increase as well.